BIBLIOMETRIC ANALYSIS OF ACUPUNCTURE RESEARCH FRONTS AND THEIR WORLDWIDE DISTRIBUTION OVER THREE DECADES - Fu, Jun-Ying; Zhang, Xu; Zhao, Yun-Hua; Tong, He-Feng; Chen, Dar-Zen; Huang, Mu-Hsuan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Considerable research has been conducted on acupuncture worldwide. This study chronologicallyexamined the changing features and research fronts of acupuncture and elucidated the differences among the six mostproductive countries.Methods: Bibliographic coupling is a powerful tool for identifying the research fronts of a field. Acupuncture-relatedpublications worldwide and from the six most productive countries during 1983–2012 were retrieved from the ScienceCitation Index Expanded and Social Science Citation Index. To form the research fronts, the 100 most highly citedpapers (HCPs) were clustered in terms of references shared.Results: The United States had the highest proportion of HCPs. The effectiveness of acupuncture in areas such asrelieving neck and back pain, migraines and headaches, and knee osteoarthritis symptoms was a predominant topic.Initially, the endogenous opioid peptide system was the primary research focus in the acupuncture mechanism research;however, during 1993–2012, researchers focused more on the functional magnetic resonance imaging of brain activity.In addition, acupuncture use and prevalence, the attitudes of health practitioners, and the effects of expectancy andbelief were also major topics. Researches from Western countries, including the United States, England, and Germany,showed more interest in clinical trials and economic- and ethics-related studies, whereas those from East Asiancountries including China, Japan, and South Korea focused more on mechanism research.Conclusion: Western countries dominated the research fronts of acupuncture. The patterns of the research fronts variedworldwide, indicating continuity and innovation in research in each country.